Indications of caesarean section in a tertiary care teaching hospital - Bhardwaj, Davinder; Bhardwaj, Bikram; Mane, Jitendra D; Nandy, Souvik; Bhattacharya, Ritam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The rising trend of caesarean deliveries is noticed across the globe. The caesarean deliveries are associated with costlier health care, increased risk of maternal and perinatal morbidity as compared to vaginal deliveries. This study was aimed to find out the rate and various indications of caesarean deliveries and to amend the current protocols based on these findings to reduce the incidence of caesarean in our institute in future. Methods: A cross sectional observational study was done to find the caesarean delivery rate and various indications contributing to it for a period of one year. All pregnant women with period of gestation more than 28 weeks who delivered in hospital were included in the study. All women with period of gestation less than 28 weeks and in labour irrespective to mode of delivery and foetal outcome were excluded from the study. Results: The overall Caesarean section (CS) rate was 34.23% out of 2676 deliveries. The commonest indication was repeat CS (45.09%) followed by foetal distress (12.66%), failed induction (12.34%) and arrest of labour (10.26%). The commonest cause for the repeat CS was patient refusal for trial of labour 195 (47.22%). Conclusions: The common indications of CS found are repeat CS, Foetal distress, NPOL and failed induction. Foetal distress, NPOL and failed induction are amenable to intervention and needs to be introspected at institutional levels. Trial of labour after CS (TOLAC) should be encouraged to control the rising trend of CS.